TECHNOLOGY IN EDUCATION; TPACK AS AN APPROACH TO BECOMING A REVOLUTIONARY TEACHER IN THE DIGITAL AGE - Hambali, Hambali; Rozi, Fathor; Mardiya, Mardiya (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to analyze the readiness of educators as revolutionary teachers in the digitalization era through the TPACK (technology, pedagogy, content, knowledge) approach to Islamic Elementary School Teacher Education students and teachers at MI Al-Islamiyah Karanganyar Paiton. This study uses a qualitative approach with a case study type of research. Data collection techniques were carried out by interviews and observation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this study indicate that preparing to become a revolutionary teacher in the digital era takes several steps, namely; strengthening personal branding, increasing teacher competence TPACK and having tech savvy abilities. This research has implications with the use of the TPACK approach, can prepare themselves to become revolutionary teachers who are able to combine their knowledge with the rapid development of technology in this digital era.